2015
DOI: 10.1039/c5tx00012b
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ethanol exposure induces an intrauterine programming of enhanced sensitivity of the hypothalamic–pituitary–adrenal axis in female offspring rats fed with post-weaning high-fat diet

Abstract: Our previous study demonstrated that prenatal ethanol exposure (PEE) enhances the sensitivity of the hypothalamic-pituitary-adrenal (HPA) axis in adult offspring rats. This study aims to investigate the underlying mechanism. PEE treated female offspring rats were fed with high-fat diet and subjected to the unpredictable chronic stresses (UCS) in adulthood. For adult offspring, the PEE group exhibited increased expression of hypothalamic corticotrophin-releasing hormone (CRH) and arginine vasopressin (AVP) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, the upregulation of hippocampal GAD67 was not observed in the PEE female offspring in the same experiment (Supplementary Fig. 1 ), suggesting that the mechanism for the enhanced potential excitatory ability of hypothalamus is gender-specific 32 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, the upregulation of hippocampal GAD67 was not observed in the PEE female offspring in the same experiment (Supplementary Fig. 1 ), suggesting that the mechanism for the enhanced potential excitatory ability of hypothalamus is gender-specific 32 .…”
Section: Discussionmentioning
confidence: 78%
“…Detailed protocols for total RNA extraction, reverse transcription and qRT-PCR were reported in our previous study 32 . The sequences and annealing conditions for the genes are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Glucocorticoids could repress IGF1 expression in multiple types of organs and cells via GR activation (24, 25), and decreased IGF1 expression could further inhibit the expression of ISL1 (53), which is one of the most important transcription factors involved in the regulation of pancreatic development and insulin expression (54). In our previous researches, we have demonstrated that PEE could induce fetal over-exposure to maternal glucocorticoids in utero (26, 55, 56), which further increased the GR expression [e.g., hippocampus (56) and adrenals (26)] and decreased IGF1 expression [e.g., adrenals (26), and liver (28)] of multiple fetal organs, and thus resulted in their developmental programming alterations. In addition, in other IUGR models induced by prenatal exposure to xenobiotics [such caffeine (57), nicotine (58)], we have also found the fetal over-exposure to maternal glucocorticoids, and the alterations of GR expression in multiple fetal organs, accompanied with related developmental programming changes.…”
Section: Discussionmentioning
confidence: 99%